An Instant Relationship Between Hyponatremia, Geriatric Syndromes, and Drugs in Older Adults: A Cross-Sectional Analysis from a Single Geriatric Clinic - Ali Ekrem Aydin; Esra Ates Bulut; Suleyman Emre Kocyigit; Fatma Sena Dost; Feyza Mutlay; Kubra Altunkalem Seydi; Fethiye Esenkaya; Ahmet Turan Isik (Diagnostics)
Background: Hyponatremia is a common electrolyte disorder in older adults that can lead to poor clinical outcomes and increased mortality. This study aims to evaluate the interrelationship between hyponatremia and geriatric syndromes and drugs in older adults. Methods: This study included 1100 elderly patients admitted to a geriatric clinic. Patient records were used to obtain demographic information, comorbidities, geriatric syndromes, medications, laboratory results, and comprehensive geriatric assessment parameters. Results: The prevalence of hyponatremia was 23.9% in this study (mean age ± SD was 75.59 ± 8.13 years). The frequency of polypharmacy, dementia, falls, malnutrition and risk of malnutrition, frailty, probable sarcopenia, hypertension, cerebrovascular disease, and congestive heart failure was higher, and patients were older in the hyponatremia group (p < 0.05) than in the normonatremia group. After the adjustment of covariates, hyponatremia was shown to be related to drugs including escitalopram (odds ratio [OR]: 1.82, 95% confidence interval [CI]: 1.20–2.76), trazodone (OR: 2.27, 95% CI: 1.26–4.10), renin angiotensin aldosterone system (RAAS) inhibitors (OR: 1.71, 95% CI: 1.18–2.47), hydrochlorothiazide (OR: 1.83, 95% CI: 1.28–2.62), and opioids (OR: 4.46, 95% CI: 1.24–16.02) (p < 0.05). Polypharmacy, falls, and malnutrition with risk of malnutrition were still significantly associated with increased hyponatremia risk even after adjustment for age, sex, and comorbidity burden (p < 0.05). Conclusions: Hyponatremia seems to be associated with certain geriatric syndromes, as well as the use of some antidepressants and cardiovascular drugs in older adults. Malnourished older adults taking RAAS inhibitors, diuretics, opioids, and antidepressants may be at a higher risk of developing hyponatremia. They should be closely monitored, especially if they are taking multiple medications.